2022
DOI: 10.3390/plants11020149
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Macro- and Microelements, and Trace Metals in Spring Wheat Genetic Resources in Siberia

Abstract: Western Siberia is one of the major spring wheat regions of Russia, cultivating over 7 Mha. The objective of the study was to evaluate the variation of macro- and microelements, and of trace metals in four distinct groups of genetic resources: primary synthetics from CIMMYT (37 entries), primary synthetics from Japan (8), US hard red spring wheat cultivars (14), and material from the Kazakhstan–Siberian Network on Spring Wheat Improvement (KASIB) (74). The experiment was conducted at Omsk State Agrarian Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…For example, the mean values for Mn and Fe, 6.1 and 12.6 mg kg −1 , respectively, are comparable with previous measurements of 8 and 13 mg kg −1 [ 27 ], and 10 and 12 mg kg −1 [ 28 ], respectively. The concentrations of Fe, Cu, and Zn reported here agree with a report on Iranian wheat [ 2 ], and the Zn and Cd concentrations agree with reports on Chinese wheat [ 24 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For example, the mean values for Mn and Fe, 6.1 and 12.6 mg kg −1 , respectively, are comparable with previous measurements of 8 and 13 mg kg −1 [ 27 ], and 10 and 12 mg kg −1 [ 28 ], respectively. The concentrations of Fe, Cu, and Zn reported here agree with a report on Iranian wheat [ 2 ], and the Zn and Cd concentrations agree with reports on Chinese wheat [ 24 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Biofortification is a sustainable and cost-effective solution that relies on selecting genotypes with accepted levels of metal accumulation and dissecting the genetic architecture underlying their natural variation [ 8 , 9 , 24 , 25 , 26 ]. We selected the best performing genotypes based on different criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The series of ionomics studies with spring wheat in the region allows the development of a breeding strategy and methodology to enhance the elemental composition. Two previous ionomics studies in Northern Kazakhstan and Western Siberia [14,15] demonstrated a large effect of protein content on the concentration of both macro-and microelements. Concentrations of Fe, Mn, and S were positively correlated with protein content on both environment and genotype levels.…”
Section: Breeding Approaches Based On the Study Resultsmentioning
confidence: 91%
“…The third study focused on the spring wheat genetic diversity panel (GDP) assembled to enhance agronomic and quality traits at Omsk State Agrarian University [15]. The panel comprised three groups of germplasm: primary hexaploid synthetics (CIMMYT and Japan origin), cultivars from Kazakhstan and Russia (primarily KASIB network), and USA cultivars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation